(untitled) (Itinera, 2024)
When developing an aesthetics of VR, it is essential that it remains anchored to concrete objects and actual users’ inclinations and practices. This article provides an example of an “experience-based” aesthetics of VR, presenting the results of a pilot empirical study on fear in VR and discussing it in aesthetic terms. More in particular, the article ventures into two important debates in the field: that around the “paradox of fiction”, and that concerning aesthetic distance. By doing so, the article highlights the fruitfulness of investigating a difficult object like VR, which eludes standard conceptualizations from image and media theory. At the same time, it illustrates how developing a specific aesthetics of VR can contribute in turn to indicate new pathways into long-standing issues in aesthetics as a whole.